The effectiveness of cement lime to reduce detergents content in domestic wastewater - Slamet, Agus; Voijant Tangahu, Bieby; Yuniarto, Adhi (International Journal of Engineering and Technology, 2019)
The content of detergent in the domestic wastewater which is disposed directly to the river has been cause inhibition in transfer of oxygen mass into water. The Ca ions can be used to reduce activity of detergent in the domestic wastewater. The Ca ions will bind Na ions and phosphate compound in the detergent through precipitation reactions. The granular media from cement lime was used as filter media to release of Ca ions. The aims of the research were to find the composition of cement lime which is capable to release Ca ion which capable to reduce detergent activity. Jar test experiments have been conducted to find the optimum composition of lime cement media in reducing detergent concentration in domestic wastewater, the composition of lime cement with a ratio of 1:1 to 6:1. Furthermore, the optimum composition of lime cement medium was used as a filter medium to treat domestic wastewater. The filter is operated with a continuous flow. The result showed that the composition of lime - cement media 6:1 was able to reduce detergent concentration up to 88.65 % with initial concentration 122.6 mg/L.Â Â